PENDEKATAN TERKINI DALAM DIAGNOSIS DAN TATA LAKSANA NEUROSIFILIS - Satiti, Sekar; Bayuangga, Halwan Fuad; Aifa, Bardatin Lutfi (PERDOSNI, 2025)
Neurosyphilis is a manifestation of Treponema pallidum infection involving the central nervous system which may occur at any stage of syphilis. This condition remains a global health concern with increasing incidence, particularly among individuals coinfected with human immunodeficiency virus (HIV). Its broad and often nonspecific clinical spectrum poses significant challenges for both diagnosis and management. This review discusses current approaches to the diagnosis and management of neurosyphilis based on the latest guidelines from the Centers for Disease Control and Prevention (CDC), the British Association of Sexual Health and HIV (BASHH), and the European Guidelines. The diagnosis of neurosyphilis is established through the integration of clinical findings, treponemal and nontreponemal serologic tests, and cerebrospinal fluid (CSF) analysis. Parenteral penicillin G for 10–14 days remains the first-line therapy in all major international guidelines. Ceftriaxone, doxycycline, or a combination of amoxicillin and probenecid may serve as alternative regimens in patients with penicillin allergy, although penicillin desensitization is still recommended whenever feasible. Corticosteroids, such as prednisolone, may be used prophylactically to prevent the Jarisch–Herxheimer reaction. Post-treatment monitoring through periodic clinical, serologic, and CSF evaluations is essential to ensure eradication of infection and prevent reinfection. A comprehensive diagnostic approach, early detection, appropriate antimicrobial therapy, and long-term follow-up are key determinants for improving outcomes in patients with neurosyphilis. Keywords: neurosyphilis, Treponema pallidum, neurosyphilis diagnosis, penicillin G, ceftriaxone